Release of The Rights on Management of PT. Indonesian Port III, (Persero) To The Certificate of Land And Building Connected to Marine Tourism Village in Semarang - M. Ali Mashar; Akhmad Khisni (Jurnal Akta, 2018)
Land is a natural resource that is essential for human survival. But this time the land is a natural resource that is finite and diminishing. Land has many proprietary someone (private) and state-owned land has been extremely limited. Based on the background mentioned above have been presented, the authors are interested to examine, discuss and review the above issues in the form of a study entitled: " Release Of The Rights On Management Of PT. Indonesian Port III, (Persero) To The Certificate Of Land And Building Connected To Marine Tourism Village In Semarang”. The results are expected to contribute ideas for the development of legal science in particular on how the waiver process management PT. Indonesian Port III, The method used is qualitative analysis. Based on the formulation of the problem it is concluded HPL release the legal basis must be based on legislation, if not yet published legislation, it can be subjected to a government regulation to replace legislation or government regulation (a regulation). HPL release law committed by PT. Pelindo on land certificates are fully controlled by people of Tambak Lorok so that the transition will not happen obstacles.Keywords: Release; Right On Management; PT. Indonesian Port III (Persero); Semarang.